2019
DOI: 10.1186/s13045-019-0748-z
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in cancer therapy resistance and targeted drug development

Abstract: Noncoding RNAs (ncRNAs) represent a large segment of the human transcriptome and have been shown to play important roles in cellular physiology and disease pathogenesis. Increasing evidence on the functional roles of ncRNAs in cancer progression emphasizes the potential of ncRNAs for cancer treatment. Here, we summarize the roles of ncRNAs in disease relapse and resistance to current standard chemotherapy and radiotherapy; the current research progress on ncRNAs for clinical and/or potential translational appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
157
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(157 citation statements)
references
References 130 publications
0
157
0
Order By: Relevance
“…Studies have reported that the long non-coding RNA (lncRNA) RP11 promotes colorectal cancer cells dissemination by ZEB1 overexpression, whereas lncRNA HCCL5 could be activated by ZEB1 to promote hepatocellular carcinoma malignancy. 18,19 Among these, lncRNAs are a class of ncRNAs of more than 200 bp that have been demonstrated to be closely related to cancer progression, including tumorigenesis, 20 stemness, 21 apoptosis, 22 25 It has also been reported that LINC00511 promotes proliferation in pancreatic ductal adenocarcinoma, 26 ovarian cancer 27 and glioma. 16,17 Non-coding RNAs (ncRNAs) are transcribed genes that are not further translated into proteins and include lncRNAs, circular RNAs (circRNAs) and miRNAs, which perform vital roles in human cancers.…”
mentioning
confidence: 99%
“…Studies have reported that the long non-coding RNA (lncRNA) RP11 promotes colorectal cancer cells dissemination by ZEB1 overexpression, whereas lncRNA HCCL5 could be activated by ZEB1 to promote hepatocellular carcinoma malignancy. 18,19 Among these, lncRNAs are a class of ncRNAs of more than 200 bp that have been demonstrated to be closely related to cancer progression, including tumorigenesis, 20 stemness, 21 apoptosis, 22 25 It has also been reported that LINC00511 promotes proliferation in pancreatic ductal adenocarcinoma, 26 ovarian cancer 27 and glioma. 16,17 Non-coding RNAs (ncRNAs) are transcribed genes that are not further translated into proteins and include lncRNAs, circular RNAs (circRNAs) and miRNAs, which perform vital roles in human cancers.…”
mentioning
confidence: 99%
“…Several biomarkers have been reported to be able to predict the e cacy of anthracycline-based chemotherapy in breast cancer, for example, the expression levels of CREB3L1 in TNBC responsive to doxorubicin-based chemotherapy were signi cantly higher than that in resistant cancers [14], and loss of FKBP12 function in invasive breast cancers predicts poor prognosis and chemoresistance to doxorubicin [15] while HOXD3 overexpression enhances breast cancer cell drug resistance via integrin β3-mediated Wnt/β-catenin signaling [16]. Recently, increasing evidence has supported that ncRNAs also play an important role in drug resistance of breast cancer [17,18]. Among these ncRNAs, lncRNAs, as the promising molecular markers for forecasting drug resistance of breast cancer, are becoming new targets for treating breast cancer in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of drug resistance to chemotherapeutic agents is not fully elucidated. Currently, more and more evidences have been proved that non-coding RNAs play critical roles in drug resistance [3][4][5][6]. ncRNAs including long non-coding RNAs (lncRNAs), microRNAs (miRNAs), circular RNAs (circRNAs), and PIWI-interacting RNAs (piRNAs) are suggested to be the potential promising therapeutic targets for overcoming drug resistance in the treatment of human cancers [7][8][9][10].…”
Section: To the Editormentioning
confidence: 99%